A Qualitative Study of Career Guidance from a Health-Promoting Perspective in Norway - Roger Kjærgård; Siw Gudbrandsen (Nordic Journal of Transitions, Careers and Guidance)
This article shows how career guidance from a health-promoting perspective is experienced and can be relevant when following up on sickness absences in Norway. 35 people on sick leave were offered career guidance. Five of these participants were later interviewed about their experiences with career guidance. An interpretative phenomenological analysis is used to explore the interviewees’ experiences. The results show that the informants’ experiences included themes of recognition and equality, process time and room for reflection, liberating dialogues and mapping and concretisation. The results are then further discussed from a health-promoting perspective and show that career guidance may open opportunities for future participation in working life and give individuals confidence in their resources and abilities. Abstrakt Denne artikkelen viser hvordan karriereveiledning i et helsefremmende perspektiv oppleves og kan være relevant ved oppfølging av sykefravær. 35 sykemeldte fikk tilbud om karriereveiledning. Fem av disse deltakerne ble senere intervjuet om sine erfaringer med karriereveiledning. En fortolkende fenomenologisk analyse brukes for å utforske intervjuobjektenes erfaringer. Resultatene viser at informantenes erfaringer inkluderte temaer om anerkjennelse og likeverd, prosess tid og rom for refleksjon, frigjørende dialoger og kartlegging og konkretisering. Resultatene diskuteres deretter fra et helsefremmende perspektiv og viser at karriereveiledning kan åpne muligheter for fremtidig deltakelse i arbeidslivet og gi den enkelte tillit til sine ressurser og evner. Nyckelord: Sykefravær; karriereveiledning; oppfølging; helsefremmende